Variation in the Rate of Surgery for Ulnar Collateral Ligament Injury of the Metacarpophalangeal Joint of the Thumb. (September 2017) - Stoop, Nicky; Teunis, Teun; Ring, David; Eberlin, Kyle R.
Background: The indications for repair of rupture of the ulnar collateral ligament (UCL) of the metacarpophalangeal (MP) joint of the thumb are debated. We studied factors predictive of operative treatment.Methods: In this retrospective study, we queried the research database from 3 affiliated urban hospitals in a single city in the United States and identified 383 patients with a thumb MP UCL injury. We recorded age, sex, treating surgeon, and whether or not a magnetic resonance imaging (MRI) was ordered. If radiographs showed a concomitant avulsion fracture, we measured fragment size and displacement. Multivariable logistic regression was used to identify factors independently associated with surgery.Results: Surgery was independently associated with older patient age, widely displaced fractures (≥2 mm), and obtaining an MRI. Two specific surgeons were less likely to operate. Compared with patients without a fracture, fractures without displacement were less likely to have surgery.Conclusions: The rate of surgery for acute thumb MP UCL injury varies based on patient characteristics and the individual treating surgeon. Variation might decrease with improved diagnostic techniques and consideration of practice guidelines. Future studies are needed to determine the patients and injuries that will benefit most from surgery.